Human Capital Management Analysis using a Practice-Based Approach for Business Development at PT - Alieza Maudy Sardani; Hafiza Adlina (PT FORMOSA CENDEKIA GLOBAL, 2023)
PT X realizes that Human Capital Management is a very important asset that contributes to business development through management practices in accordance with the needs of the company. This study aims to analyze the practice-based approach of how human capital management implemented by employees affects business development in PT X. This study uses descriptive qualitative methods. The data collection techniques in this study are through observation, interviews, documentation studies, and triangulation. The results of this study indicate that human capital management implemented by employees runs quite well and influences business development at PT X. -Paced Environment.